1984
DOI: 10.1002/app.1984.070290220
|View full text |Cite
|
Sign up to set email alerts
|

New aspects in cationization of lignocellulose materials. II. Distribution of functional groups in lignin, hemicellulose, and cellulose components

Abstract: SynopsisThe distribution of functional groups in the three main components of beech after alkylation with 3-chlor-2-hydroxypropyltrimethylammoniumchloride (CHMAC) was studied. By fractional extraction of hemicellulose combined with delignification it was found that the three components were substituted to various extents. The exchanging capacity decreased in the following order: hemicellulose, lignin, and cellulose. The obtained degree of substitution is related to the accessibility and reactivity of the indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Additionally, Antal et al (1984a) found the effect of CHMAC modification on beech sawdust to be limited to the cell wall surface. Since lignin created a network across the cell wall surface, Antal et al (1984b) found the quaternization reaction with cellulose to be hindered. Moreover, Ebringerova et al (1986) also indicated that the delignification of lignocellulosic byproducts would increase reaction efficiency with CHMAC.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Antal et al (1984a) found the effect of CHMAC modification on beech sawdust to be limited to the cell wall surface. Since lignin created a network across the cell wall surface, Antal et al (1984b) found the quaternization reaction with cellulose to be hindered. Moreover, Ebringerova et al (1986) also indicated that the delignification of lignocellulosic byproducts would increase reaction efficiency with CHMAC.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of cationic xylan can be performed by cationization of xylan-rich lignocellulosic material followed by water/alkaline extraction and isolation of the modified xylan (e.g. Antal et al 1984;Š imkovic et al 1990), or it can be done directly by cationization of pre-isolated and purified xylan (e.g. Ebringerová et al 1994;Schwikal et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Navarro et al 3 synthesized an adsorbent for heavy metals by reacting cellulose with epichlorohydrin and polyethyleneimine and obtained a product with an adsorption capacity of 1.44 mmol g −1 for mercury. Antal et al 4,5 described the preparation and distribution of functional groups in lignocellulosic material after reaction with N-(3-chloro-2-hydroxypropyl) trimethylammonium chloride. The effect of the reaction was found to be limited to the cell wall surface using beech sawdust as the source of lignocellulose.…”
Section: Introductionmentioning
confidence: 99%